Development of sustainable production indicators using the analytical hierarchy process for the petrochemical industry in Malaysia / Vijayalakshmi Benjamin Samuel - Vijayalakshmi, Bejamin Samuel (2016)
The objectives of this original research was to identify sustainable production indicators (SPIs) for the petrochemical industry in Malaysia, prioritise them in order of importance and establish a methodology for the assessment of sustainable production using the Lowell Centre Indicator Framework developed by the Lowell Centre for Sustainable Production (LCSP) at the University of Massachusetts Lowell, US. The petrochemical industry was selected because it is energy intensive, generates significant impacts and has high dependence on non-renewable fossil fuels. The SPIs were identified and shortlisted from the Global Reporting Initiative (GRI) Guidelines 3.1 by the research respondents comprising EHS managers from 13 petrochemical plants in Malaysia. Out of the 81 indicators listed under six main categories of the guidelines, 19 indicators were shorlisted and prioritised using the Analytical Hierarchy Process (AHP). The commercial PC-based software, Expert Choice™ was used to calculate the weights. The findings of the research indicated that for the six categories evaluated, Environment was ranked as the SPI with the highest priority (0.3777), followed by Labour Practices and Decent Work (0.197), Society (0.133), Economy (0.106), Product Responsibility (0.102) and Human Rights (0.057). For the ranking involving the indicators from all six categories, the top five global sub-criteria are as follows: (1) EN28a: Number of EHS regulatory non-compliance; (2) LA7a: Number of Loss Time Injuries (LTIs); (3): PR1a: Number of environmental, health and safety elements included in the product life cycle assessment; (4) EN6a: Percent of staff hired from local community and (5) HR4: Total number of incidents of discrimination. These indicators were then assessed against the LCSP framework to develop a methodology to understand at which sustainability level they were at and how to progress further.